Hydrocarbons as Proton Receptors and Evidences of Unconventional and Unusual π···H, p-π···H and C···H Hydrogen Bonds - de Oliveira, Boaz Galdino (Orbital: The Electronic Journal of Chemistry, 2019)
In this current work, a brief historical narrative of the most popular theories that decisively aid in the comprehension of the hydrogen bond formation is presented. As is well-known, the valence bond theory was efficiently suitable to certify the electronic structure of Lewis acids/bases, in particular the fluorine, oxygen and nitrogen as high charge density sources, and as such the homodimers of 2(HF), 2(H2O) and 2(NH3) were framed as reference systems. Regarding the π bonds of acetylene and ethylene as well as the p-π (pseudo unsaturated bond) clouds of cyclopropane, these compounds belong to a distinct group of proton receptors by which the π···H, p-π···H and C···H hydrogen bonds are formed. DOI: http://dx.doi.org/10.17807/orbital.v11i3.1399